Surgical safety checklist compliance: The clinical audit. (September 2022) - Gul, Fahad; Nazir, Maheen; Abbas, Khawar; Khan, Alishba Ashraf; Malick, Daniya Shahzad; Khan, Hashim; Kazmi, Syed Naqash Haider; Naseem, Arbab Osama
Abstract: Introduction: The surgical safety checklist consists of three components: sign-in, performed before the induction of anesthesia; time-out, performed before skin incision; and sign-out, performed immediately after skin closure or before the patient leaves the operating theatre. This study aims to assess compliance with the World Health Organization (WHO) Surgical Safety Checklist (SSC) and explore the barriers facing in properly implementing the surgical safety checklist in operation theatres of a tertiary care hospital. Methodology: The observational clinical audit was conducted in Surgical Unit I, Benazir Bhutto Hospital, Rawalpindi, Pakistan. Compliance with the surgical safety checklist was observed before and after the educational intervention. After completion of the clinical audit operating theatre staff was asked about the barriers to compliance with the surgical safety checklist using an interview sheet. Mean, and standard deviation was calculated for quantitative variables, whereas frequencies and percentages were calculated for categorical variables using SPSS version 25.0. Results: Compliance with all the steps of the surgical safety checklist was improved after an educational intervention, with the highest improvement in compliance (66.7%) observed with the Sign-out step "Count of sponges and needles & instruments complete?" Moreover, filling of the patient board and documentation of procedure in the patient file were also improved. Lack of awareness and training to follow the surgical safety checklist was the commonest barrier to compliance with the surgical safety checklist. Conclusion: Implementing the surgical safety checklist will not only upgrade the patient safety measures but also integrate teamwork skills and improve the local departmental culture. Highlights: Surgical safety checklist compliance improved after the educational intervention. The highest improvement in compliance (66.7%) was observed with the Sign-out step "Count of sponges and needles & instruments complete?". The least improvement in compliance (4.2%) was observed with the Time-out step "Confirm all team members have introduced themselves by name & role?". Lack of awareness and training was the commonest barrier to compliance with the surgical safety checklist.